Application of TiO2 nanoparticles for eco-friendly biodiesel production from waste olive oil - Mihankhah, Taraneh; Delnavaz, Mohammad; Khaligh, Nader Ghaffari (Taylor & Francis, 2018)
An environmentally benign, simple, and efficient process has been developed for biodiesel production from waste olive oil in the presence of a catalytic amount of TiO2 nanoparticles at 120°C with a conversion of 91.2% within 4 h. The present method affords nontoxic and noncorrosive medium, high yield of biodiesel, clean reaction, and simple experimental and isolation procedures. The catalyst can be recycled by simple filtration and reused without any significant reduction in its activity.